AI-DRIVEN PEDAGOGICAL APPROACHES IN CONTEMPORARY EDUCATION - Ergasheva Muqaddas Toshtemirovna (Modern American Journals, 2025)
This article examines AI-based pedagogical approaches in modern education and their impact on teaching and learning. It analyzes how AI technologies, such as adaptive learning systems, intelligent tutoring, and data-driven assessment, can enrich personalized learning and improve student outcomes. The study highlights the role of AI in supporting teachers, increasing student engagement, and promoting inclusive education. Ethical issues and the importance of responsible AI integration in educational environments are also addressed.
Keywords: Artificial intelligence, education, pedagogy, technology, adaptation, personalization.